2020
DOI: 10.1109/access.2020.3011647
|View full text |Cite
|
Sign up to set email alerts
|

An Energy-Efficient Current-Controlled Write and Read Scheme for Resistive RAMs (RRAMs)

Abstract: Energy efficiency remains one of the main factors for improving the key performance markers of RRAMs to support IoT edge devices. This paper proposes a simple and feasible low power design scheme which can be used as a powerful tool for energy reduction in RRAM circuits. The design scheme is exclusively based on current control during write and read operations and ensures that write operations are completed without wasted energy. Self-adaptive write termination circuits are proposed to control the RRAM current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Note that there are also several studies expecting to increase the write endurance by 10 12 ∼10 13 , which is similar to or slightly worse than that of DRAM (e.g., 10 14 ∼10 16 [17,57,85]). For example, [86] uses a thin metallic linear and confined pore cell structure to reduce the unavailability of set/reset switching thereby significantly increasing the endurance on writes.…”
Section: Discussion and Future Workmentioning
confidence: 76%
“…Note that there are also several studies expecting to increase the write endurance by 10 12 ∼10 13 , which is similar to or slightly worse than that of DRAM (e.g., 10 14 ∼10 16 [17,57,85]). For example, [86] uses a thin metallic linear and confined pore cell structure to reduce the unavailability of set/reset switching thereby significantly increasing the endurance on writes.…”
Section: Discussion and Future Workmentioning
confidence: 76%
“…Variability also affects the switching time. For this aspect, it has been demonstrated that switching time variability can severely degrade speed and energy consumption [16].…”
Section: A Background: Rram Technologymentioning
confidence: 99%
“…Adopting this standard pulse would lead to a final HRS resistance value close to 382 MΩ. Note that the standard RST pulse width is set to 3.5 µs to cover the worst cases during RST (i.e., tail bits in the switching parameter distributions [26,27]).…”
Section: Transient Simulationsmentioning
confidence: 99%